PENGARUH MEDIA GAWANG MENGGUNAKAN METODE DRILL TERHADAP HASIL BELAJAR SHORT PASSING PADA SISWA SMPN 3 - Efendi, Marjuin; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is "is there any influence of wicket media using drill method to the result of learning short passing soccer. The purpose of this study is to improve learning outcomes short passing soccer learning. The population in this study were students in SMP Negeri 3 Sungai Raya class VIII amounted to 265 people. Sampling in this research using purposive sampling technique that is sample determination technique with certain consideration which amounted to 40 people where 20 people as experiment class and 20 person as control class. The method used in this research is experiment with true-experimental design. Data analysis was done by using t-test (analysis of variance). Based on result of t-test in experiment class got value from ttest = 20,15, while result of t-test on control class got value from ttest = 16,25 hence seen that experiment average value higher dapi at mean value control with difference of mean value 3,90 and p value 0.000 <0,05 hence Ho rejected (Ha accepted), meaning there is increasing influence of wicket media using drill method to result of learning short passing soccer.Â Keywords: Short Passing and Goal Media.Â